1986
DOI: 10.1090/s0002-9947-1986-0860375-3
|View full text |Cite
|
Sign up to set email alerts
|

A global theory of internal solitary waves in two-fluid systems

Abstract: The problem analyzed is that of two-dimensional wave motion in a heterogeneous, inviscid fluid confined between two rigid horizontal planes and subject to gravity g. It is assumed that a fluid of constant density p+ lies above a fluid of constant density p_ > p+ > 0 and that the system is nondiffusive. Progressing solitary waves, viewed in a moving coordinate system, can be described by a pair (A, w), where the constant A = g/c2, c being the wave speed, and where w(x, r¡) + r] is the height at a horizontal pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 23 publications
2
67
0
1
Order By: Relevance
“…The first study using this approach was, apparently, made in Ref. 53. It was found that there exists maximal possible solitary wave amplitude at which it acquires a flat-top shape and tends to two infinitely separated kinks.…”
Section: Strongly Nonlinear Kdv-type Models a Stationary Waves: mentioning
confidence: 99%
“…The first study using this approach was, apparently, made in Ref. 53. It was found that there exists maximal possible solitary wave amplitude at which it acquires a flat-top shape and tends to two infinitely separated kinks.…”
Section: Strongly Nonlinear Kdv-type Models a Stationary Waves: mentioning
confidence: 99%
“…This naturally introduces the notion of conjugate states as introduced by Benjamin (1966), and computed by Turner and Vanden-Broeck (1988) and described in further detail by Amick and Turner (1986) and by Evans and Ford (1996). Values of the limiting solitary wave amplitudes for the models KdV2, KdV2N, KdV3N, KdV3Nβ 1 , KdV3Nβ c and KdVEβ c are presented in Table 2 for a range of depth ratios, and these limiting amplitudes are compared with results of the conjugate state amplitude computed using the theory of Amick and Turner (1986). For the special case of a two-layer stratification with a rigid upper surface, the environmental case under examination here, Amick and Turner (1986) obtained an analytic solution for the conjugate state.…”
Section: Comparison Of Evolution Modelsmentioning
confidence: 99%
“…Values of the limiting solitary wave amplitudes for the models KdV2, KdV2N, KdV3N, KdV3Nβ 1 , KdV3Nβ c and KdVEβ c are presented in Table 2 for a range of depth ratios, and these limiting amplitudes are compared with results of the conjugate state amplitude computed using the theory of Amick and Turner (1986). For the special case of a two-layer stratification with a rigid upper surface, the environmental case under examination here, Amick and Turner (1986) obtained an analytic solution for the conjugate state. When the Boussinesq approximation is invoked, and when their results are transposed in terms of the non-dimensional variables used herein, the conjugate state is defined simply by the relations…”
Section: Comparison Of Evolution Modelsmentioning
confidence: 99%
“…dy This allows us to solve for y as a function of (x, y/), y = y(x, ^), say. We continue to follow the technique in [8,9] and define w(xx, x2) = y(x,, 4/(x2)) -x2, (x,, x2) £ T+ .…”
Section: Notationmentioning
confidence: 99%